Leadership Styles and Work Climate: Strategies Implemented by School Principals to Promote the Well-being of Educational Staff (Innovaciones Educativas, 2025)
The Costa Rican educational system faces multiple and complex challenges. One of them corresponds to the well-being and satisfaction of educational staff, who currently face a scenario characterized by demotivation and a sharp deterioration in their mental health conditions (ANDE & ACODEHU, 2021). Recent research has underlined the importance of the principal's leadership styles and the work climate as two variables that affect the well-being, performance, and job satisfaction of educational staff. For this reason, the purpose of this research is to analyze the impact of educational leadership and the promotion of healthy work climates on teacher well-being, from the principal's perspective. The methodology used was descriptive, cross-sectional, and with a qualitative approach. The population consisted of a total of nine principals of educational centers of the Costa Rican Ministry of Public Education (MEP), from different educational cycles and modalities. Semi-structured interviews were implemented, and the results were analyzed using content analysis. The research results reveal that the interviewed principals favor a distributive and participatory leadership style. Furthermore, they implement a series of actions to promote a healthy work environment. In conclusion, it is affirmed that the leadership exercised by principals plays a determining role in promoting a healthy work climate; likewise, a more horizontal management approach is evident, committed to daily support, the team's well-being, and active participation in institutional processes.
Keywords: leadership; education; educational management; mental health; work environment